P78 The acceptability of digital self-examination in men who have sex with men (MSM) at risk of anal intraepithelial neoplasia (AIN). (23rd May 2012) - Bayley, J; Perry, N; Shaw, S; Campbell, L; Richardson, D
Abstract : Background: AIN is a pre-cancerous change in the anal mucosa caused by human papilloma virus (HPV) which untreated, may progress to anal squamous cell carcinoma with 500 new cases per year in the UK. There is currently no evidence about the efficacy of self-examination, but this may be a quick, cheap and effective screening tool to aid early diagnosis and prevent cancer. Methods: Patients attending a GU/HIV clinic were given a questionnaire exploring knowledge and risk factors of AIN and attitudes to self-examination. They were then given an educational leaflet on what to do and feel for. Inclusion criteria were males >18 years old who identified as MSM. Results on an SPSS database were analysed using standard statistical methods. Results: 103 questionnaires were returned, 60 (58%) were HIV positive. 10/103 (9.9%) were aware of AIN. 68/93 (73.1%) who were unaware of AIN wanted more information about the condition. 95/103 (92.2%) thought digital self-examination was acceptable. 55/103 (53.4%) self-examined regularly. Of people who self-examined 26/55 (47.3%) had a history of warts, compared to 12/48 (25%) with no history of warts (p=0.02). 38/48 (79.2%) who did not self-examine wanted more information compared to just 34/55 (61.8%) who regularly self-examined (p=0.06). Discussion: This study highlights a lack of awareness about AIN and the acceptability of self-examination for this condition. Over half were regularly self-examining but only a small proportion had heard of AIN, suggesting that although they are happy to self-examine, they are unsure what to look for. Most MSM wanted more information. Digital self-examination may therefore provide a rapid, cheap, effective and acceptable screening tool. This may help to diagnose AIN earlier and allow education about self-examination and information regarding AIN to be regularly incorporated into clinic visits for MSM. Further research into the efficacy of this technique for detecting AIN is required.